2014
DOI: 10.1111/bph.12559
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of VEGF signalling to fostamatinib‐induced blood pressure elevation

Abstract: BACKGROUND AND PURPOSEFostamatinib is an inhibitor of spleen tyrosine kinase (TK). In patients, fostamatinib treatment was associated with increased BP. Some TK inhibitors cause BP elevation, by inhibiting the VEGF receptor 2 (VEGFR2). Here, we have assessed the mechanistic link between fostamatinib-induced BP elevation and inhibition of VEGF signalling. EXPERIMENTAL APPROACHWe used conscious rats with automated blood sampling and radio telemetry and anaesthetized rats to measure cardiovascular changes. Rat is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 49 publications
6
39
0
Order By: Relevance
“…The data presented in Figures and suggest a close alignment between the PKPD relationship for VEGFR‐2‐mediated blood pressure effect in both humans and rats. A number of other publications have also shown that VEGFR‐2‐inhibiting compounds known to cause hypertension in humans also cause blood pressure elevation in rats (Banfor et al, ; Isobe et al, ; Skinner et al, ; Carter et al, ). These data therefore suggest that the role of VEGFR‐2 in regulating blood pressure is conserved in both species.…”
Section: Discussionmentioning
confidence: 95%
“…The data presented in Figures and suggest a close alignment between the PKPD relationship for VEGFR‐2‐mediated blood pressure effect in both humans and rats. A number of other publications have also shown that VEGFR‐2‐inhibiting compounds known to cause hypertension in humans also cause blood pressure elevation in rats (Banfor et al, ; Isobe et al, ; Skinner et al, ; Carter et al, ). These data therefore suggest that the role of VEGFR‐2 in regulating blood pressure is conserved in both species.…”
Section: Discussionmentioning
confidence: 95%
“…Off-target inhibition of VEGFR2 was found to increase vascular resistance and reduced VEGF-induced nitric oxide release in animal models [50], where effects were dose-dependent, but effectively managed by drug withdrawal or concomitant treatment with antihypertensive agents [51]. R406 also inhibited VEGF-dependent human endothelial cell tube formation and tube outgrowth, further supporting a possible role for VEGF signaling in blood pressure effects of fostamatinib [48].…”
Section: Spleen Tyrosine Kinase Inhibitionmentioning
confidence: 89%
“…In a separate kinase screen, VEGFR2 was identified as a secondary target of fostamatinib and further evaluated as a possible mechanism for the elevated blood pressure and increased incidence of hypertension previously observed in clinical studies of fostamatinib [47,50]. Off-target inhibition of VEGFR2 was found to increase vascular resistance and reduced VEGF-induced nitric oxide release in animal models [50], where effects were dose-dependent, but effectively managed by drug withdrawal or concomitant treatment with antihypertensive agents [51].…”
Section: Spleen Tyrosine Kinase Inhibitionmentioning
confidence: 99%
“…The effect of fostamatinib on blood pressure elevation (mean increase of ∼3 mm Hg in both systolic and diastolic) appeared to be dose dependent, and a concentration-dependent increase of blood pressure was observed with increasing R406 concentrations. Fostamatinib-induced hypertension may be attributed to increased vascular resistance, secondary to reduced vascular endothelial growth factor-induced nitric oxide release from endothelium [55]. Blood pressure usually returns to normal upon decrease in fostamatinib dose or its withdrawal.…”
Section: Syk As a Therapeutic Targetmentioning
confidence: 99%